2005
DOI: 10.1097/01.brs.0000171911.99348.90
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Illness of Chronic Low Back Pain in Sweden

Abstract: In Sweden, the indirect costs for chronic LBP appear to be substantially higher than the direct costs for pharmaceuticals, medical visits, physiotherapy, andhospitalizations. The high indirect costs indicate that more effective treatments for chronic LBP could potentially lead to cost savings even if the therapy costs were higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(56 citation statements)
references
References 30 publications
7
44
2
3
Order By: Relevance
“…In our study, the mean annual cost associated with productivity losses represented about 40% of the total direct health care and productivity costs. This proportion is consistent with earlier observations made in individuals suffering from fibromyalgia syndrome55 and chronic low back pain54 where the proportion of costs associated with productivity losses accounted for more than half of the total costs. Similar observations were also made by Guerriere et al24 in a population of chronic pain patients waiting for treatment in tertiary care pain clinics.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, the mean annual cost associated with productivity losses represented about 40% of the total direct health care and productivity costs. This proportion is consistent with earlier observations made in individuals suffering from fibromyalgia syndrome55 and chronic low back pain54 where the proportion of costs associated with productivity losses accounted for more than half of the total costs. Similar observations were also made by Guerriere et al24 in a population of chronic pain patients waiting for treatment in tertiary care pain clinics.…”
Section: Discussionsupporting
confidence: 92%
“…When combined, the direct health care costs and productivity costs led to mean annual total costs of CAD $16,636 per patient, which compares with previous estimates in fibromyalgia (US $15,000 [2009 values]; CAD $15,489 [2011 values]),56 chronic low back pain (US $19,473 [2002 values]; CAD $23,566 [2011 values]),54 and osteoarthritis (US $16,146 [2005 values]; CAD $18,189 [2011 values]) 57. Other studies have also reported that economic burden increases with the severity of pain disability.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…1 Management of chronic pain requires a range of services, including general practitioner (GP) visits, specialist visits, investigations, physical therapy, hospital admissions, and prescription of pain medications. The costs of these services arc substantial (see Table 1) [5][6][7][8][9][10][11][12][13] Journal of Pain & Palliative Care Pharmacotherapy 71 …”
Section: Cost To Health Care Systemsmentioning
confidence: 99%
“…About 10% of the patients with back pain proceed with surgical operation to treat the pain [7]. The annual direct costs for patients with chronic back pain are around EUR 3,100 per patient, and the indirect costs are around EUR 17,600, which makes chronic back pain one of the main burdens for the health care system [8, 9], and consequently preventing chronification a prime target. Every effective pain treatment, treating the cause of the pain, would be a massive benefit for patients, an important medical progress, and a valuable support for the healthcare system.…”
Section: Introductionmentioning
confidence: 99%